Corrosion-resistant filler based on tannic acid modified load corrosion inhibitor ZIF, preparation method and application
By using the tannin acid -modified load corrosion -corrosion filler in the anticorrosive coating, the problem of being easily damaged and the corrosion agent is added during the long -term service of existing coating. Repair and protective performance.
Patent Information
- Application Number
- CN202411447756.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-21
AI Technical Summary
Existing anticorrosion coatings are susceptible to external conditions during long-term service and the direct addition of corrosion inhibitors may damage the integrity of the coating and reduce protective performance.
Tannic acid modified loaded corrosion inhibitor ZIF anti-corrosion filler is used to prepare a zeolite imidazolic acid framework loaded with benzimidazole, and its surface is modified into a tannic acid-based BI@ZIF-8@TA structure, combined with the ring Oxygen resins are used to prepare anti-corrosion coatings.
It improves the load and release efficiency of the coating, enhances the self -repair ability and protection performance of the coating, and significantly improves the anticorrosive effect of the metal substrate.
Smart Images

Figure CN119331452A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of anti-corrosion coatings, and specifically relates to an anti-corrosion filler based on tannic acid-modified loaded corrosion inhibitor ZIF, a preparation method and an application thereof. Background Art
[0002] Metal components of marine engineering equipment are inevitably corroded during long-term service, which in turn affects their safety. In the past few decades, people have continuously developed various methods to prevent metal corrosion, such as coating with organic coatings. Organic coatings act as physical shields, which can isolate the metal substrate from corrosive media, slow down the corrosion cathode and anode reactions, and thus hinder the corrosion process of the metal. However, during the service of the equipment, the coating will inevitably be affected by various external conditions, resulting in damage, cracking and other phenomena. If it is not repaired in a timely and effective manner, the protective effect of the coating on the metal substrate will be greatly reduced.
[0003] Self-healing coatings have anti-corrosion effects and self-repairing capabilities, which can extend the service life of the coating and reduce maintenance costs. The research and development of this type of coating has become a research hotspot at home and abroad. If the two methods of coating and adding corrosion inhibitors are used in combination, it can not only prolong the time for corrosive particles to reach the surface of the metal substrate, but also effectively protect the metal substrate at the defects of the coating. However, adding corrosion inhibitors directly to the coating may destroy the integrity of the coating, resulting in poor protective performance of the coating. Therefore, encapsulating the corrosion inhibitor into micro- or nano-containers for protective coatings is an effective way to solve the above problems. Such micro- or nano-containers can release corrosion inhibitors under the stimulation of external conditions, such as temperature, light, corrosive particles, pH value, and corrosion potential.
[0004] In recent years, metal organic frameworks (MOFs) have become a new type of nanoporous material that has attracted much attention. Due to their large surface area, adjustable composition, and high porosity, they are widely used in gas separation, drug delivery, and catalysis. At the same time, the application of MOFs in the field of corrosion protection has attracted the attention of researchers. Zeolitic imidazolic acid framework-8 (ZIF-8) has the advantages of pH-sensitive release behavior, high chemical stability, and easy synthesis. It is a suitable tool for controlling drug delivery and can be used as a pH-responsive nanocarrier that loads corrosion inhibitors and releases them in a controllable manner. Therefore, it is of great significance to use ZIF-8 as a carrier to prepare MOFs particles loaded with corrosion inhibitors. Tannic acid (TA), as a green corrosion inhibitor, can chelate with metal ions to form a passivation film on the surface of the metal matrix and thus slow down the corrosion of the metal. In order to further extend the protective performance of the coating, it is a good choice to modify the MOFs particles loaded with corrosion inhibitors using TA for the preparation of anti-corrosion coatings. In the prior art, the preparation method of the corrosion inhibitor-loaded BTA@ZIF-8 / BN-OH composite powder disclosed in document CN115353763A is to grind and mix sodium hydroxide, potassium hydroxide, and hexagonal boron nitride two-dimensional materials, rinse with deionized water, and transfer to a reactor; react at 180°C for 2h; centrifuge and take the supernatant to obtain a hydroxylated boron nitride two-dimensional material BN-OH dispersion; add zinc nitrate hexahydrate and deionized water and stir evenly; then add 2-methylimidazole, benzotriazole and anhydrous ethanol, and react for 12h in a 25°C water bath and stirring conditions; separate, wash, precipitate and dry to obtain a composite powder; add the composite powder and the dispersion to a sol-gel ceramic anticorrosion coating and stir evenly; then cover the mixed coating on the surface of the substrate by spraying or coating; and cure at 170°C for 1h to obtain a coating with a slow-release anticorrosion function. Although this scheme uses a one-step method to prepare composite powders, it still has shortcomings such as a low corrosion inhibitor loading amount. In addition, the preparation method does not further modify it to enhance the protective performance of the coating, and has defects such as being unable to achieve long-term corrosion protection of the coating. Summary of the invention
[0005] In view of the above-mentioned shortcomings of the prior art, the present invention provides a tannic acid-modified loaded corrosion inhibitor ZIF anticorrosive filler, a preparation method and application. To achieve the above-mentioned purpose, the scheme of the present invention is as follows: In a first aspect, the present invention provides a method for preparing a tannic acid modified loaded corrosion inhibitor ZIF anticorrosive filler, comprising the following steps: S1. Preparation of zeolite-type imidazole acid framework loaded with benzimidazole (BI); S2. The zeolite-type imidazole acid skeleton loaded with benzimidazole is modified by using tannic acid to obtain the anti-corrosion filler.
[0006] Optionally, in step S1, a zeolite-type imidazole acid framework loaded with benzimidazole is prepared, comprising: adding a zinc salt-alcohol solution and a dimethylimidazole ligand-alcohol solution to a benzimidazole-alcohol solution in sequence, stirring, standing, centrifuging, washing the precipitate obtained by centrifugation, and drying to obtain the zeolite-type imidazole acid framework loaded with benzimidazole.
[0007] Optionally, the mass ratio of the zinc salt to the benzimidazole is 1-1.5:0.08-0.15.
[0008] Optionally, the zinc salt is selected from zinc nitrate (including hydrates), zinc sulfate (including hydrates), and zinc chloride (including hydrates).
[0009] Optionally, the mass ratio of the dimethylimidazole ligand (2-Melm) to the benzimidazole is 2-3:0.08-0.15.
[0010] Optionally, the drying temperature is 55-65° C., and the drying time is 12-36 hours.
[0011] Optionally, in step S2, tannic acid is used to modify the zeolite-type imidazole acid framework loaded with benzimidazole, comprising: S2.1 dissolving the benzimidazole-loaded zeolite-type imidazole acid framework in water to obtain a suspension; S2.2 Add a tannic acid solution with a pH of 7.5-8.5 to the suspension, stir, let stand, centrifuge, wash the precipitate obtained by centrifugation, and dry to obtain the tannic acid-modified loaded corrosion inhibitor ZIF anticorrosive filler.
[0012] Optionally, in step S2.2, the mass ratio of the tannic acid to the benzimidazole-loaded zeolite-type imidazole acid framework is 35-45:0.8-1.5.
[0013] Optionally, in step S2.2, the drying temperature is 65-75° C., and the drying time is 12-36 h.
[0014] In a second aspect, the present invention also provides a tannic acid modified loaded corrosion inhibitor ZIF anticorrosive filler prepared according to the method as described above.
[0015] In a third aspect, the present invention further provides an anti-corrosion coating, comprising an epoxy resin and a tannic acid-modified loaded corrosion inhibitor ZIF anti-corrosion filler prepared according to the above method. The anti-corrosion coating is prepared by the following method: mixing bisphenol A diglycidyl ether, neopentyl glycol diglycidyl ether and polyamide to obtain a mixture; adding xylene and n-butanol into the mixture to obtain a mixed system; Ultrasonic dispersion of the alcohol solution of the tannic acid modified ZIF corrosion inhibitor-loaded anticorrosive filler in the mixed system to obtain a coating liquid; The coating liquid is coated on the surface of the substrate and subjected to secondary curing to obtain the anti-corrosion coating.
[0016] Optionally, the mass ratio of bisphenol A diglycidyl ether, neopentyl glycol diglycidyl ether and polyamide is 11-12:7-8:11-12.
[0017] Optionally, the volume ratio of xylene to n-butanol is 55-65:20-30.
[0018] Optionally, the material ratio of the mixture to the xylene is 30-31 g:55-65 mL.
[0019] Optionally, the mass ratio of the tannic acid-modified loaded corrosion inhibitor ZIF anticorrosive filler to the bisphenol A diglycidyl ether is 0.08-0.15:11-12.
[0020] Optionally, the secondary curing includes: first curing at a temperature of 75-85° C. for 1.5-2.5 hours, and then curing at a temperature of 35-45° C. for 12-26 hours.
[0021] Beneficial effects of the present invention: In the present invention, the preparation of ZIF-8 and the loading of BI are carried out simultaneously, which has the advantages of simple preparation process and high corrosion inhibitor loading amount; In the present invention, the modification between BI@ZIF-8 and TA is carried out in a distributed manner, and the obtained anticorrosive filler based on tannic acid-modified loaded corrosion inhibitor ZIF has the advantages that the BI@ZIF-8 structure is not easily destroyed and the surface is effectively modified; In the present invention, the corrosion inhibitor loading amount is high and easy to release, and the prepared coating has good self-repairing effect; In the present invention, the anticorrosive filler based on tannic acid-modified loaded corrosion inhibitor ZIF has good compatibility with the EP coating, and BTA@ZIFs is easy to disperse in the coating; The anticorrosive filler based on tannic acid-modified loaded corrosion inhibitor ZIF is easy to disperse in the coating, and the corrosion inhibition efficiency of the prepared coating is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 FT-IR images of BI@ZIF-8 and BI@ZIF-8@TA; Figure 2 X-ray diffraction patterns of ZIF-8, BI@ZIF-8 and BI@ZIF-8@TA; Figure 3SEM images of ZIF-8, BI@ZIF-8 and BI@ZIF-8@TA, from top to bottom, they are ZIF-8 (corresponding to part a in the figure), BI@ZIF-8 (corresponding to part b in the figure) and BI@ZIF-8@TA (corresponding to part c in the figure); Figure 4 Figure 1 is a performance test result diagram of BI release from BI@ZIF-8, a is a curve diagram of BI standard solution, and b) is a curve diagram of BI release from ZB-2 under different pH conditions; Figure 5 The EIS test results of each coating sample after immersion for 1 day; Figure 6 The EIS test results of each coating sample after immersion for 84 days; Figure 7 Figure 2 shows the EIS test results of each coating sample after immersion for 173 days. DETAILED DESCRIPTION
[0023] The following will describe the embodiments of the present invention with reference to the accompanying drawings and preferred embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be understood that the preferred embodiments are only for illustrating the present invention, not for limiting the scope of protection of the present invention.
[0024] Zeolite imidazolate framework structure materials (ZIFs) are tetrahedral framework porous crystalline materials formed by cross-linking organic imidazolates to transition metals. Among them, ZIF-8 is a metal organic framework material composed of zinc ions and 2-methylimidazole, which is selected as a carrier for loading corrosion inhibitors; benzimidazole (BI) is a corrosion inhibitor currently commonly used for corrosion protection of metal materials such as carbon steel. The N atom with a lone electron pair in the BI molecule can form a coordination bond with the Fe atom, so that the BI molecule is adsorbed on the surface of carbon steel to form a protective film; tannic acid (TA) is a naturally occurring non-toxic water-soluble polyphenol that is widely found in plants and fruits. Tannic acid can adhere to the surface of metal, glass and polymer substrates. It can also convert rust into a protective magnetite layer and is an environmentally friendly corrosion inhibitor. In the present invention, loaded BI@ZIF-8 and BI@ZIF-8@TA are added to the epoxy resin as fillers. On the one hand, BI@ZIF-8 and BI@ZIF-8@TA have good compatibility with the EP coating, which can increase the addition amount of the sample, thereby improving the corrosion inhibition performance of BI. On the other hand, BI molecules and TA molecules can be gradually released, thereby realizing the self-healing performance of the coating. Example
[0025] S1. Preparation of BI-loaded ZIF-8 S1.1 Preparation of BI-loaded ZIF-8 Weigh 1.36 g zinc nitrate hexahydrate (Zn(NO3)2∙6H2O) and 1.5 g 2-Melm (C4H6N2) and add them into 25 mL methanol solution, respectively, and record them as solution A and solution B; Prepare 10 mL of 2 mg / mL BI-methanol solution, add solution B into the BI-methanol solution, stir for 10 min, then add solution A, stir for 0.5 h, let stand for 24 h, wash the obtained product repeatedly with methanol for 3 times, and then dry it in a vacuum drying oven at 70 °C for 24 h to obtain a BI@ZIF-8 sample.
[0026] The ZIF-8 sample was prepared according to the above method except that the BI-methanol solution was not added.
[0027] S1.2 Preparation of TA-modified BI@ZIF-8 Weigh 0.1 g BI@ZIF-8 and add it into 10 mL water, stir evenly to obtain BI@ZIF-8 suspension; Under vigorous stirring, a tannic acid solution with a pH value of 8 (concentration of 12 mol / L) was added to the BI@ZIF-8 suspension. After stirring for 15 min, the obtained product was repeatedly washed three times with a mixed solution of ethanol and water (ethanol: water = 1:9, volume ratio), and then dried in a vacuum drying oven at 70 °C for 24 h to obtain TA-modified BI@ZIF-8 (hereinafter referred to as BI@ZIF-8@TA).
[0028] BI@ZIF-8 and BI@ZIF-8@TA were characterized by Fourier transform infrared spectroscopy (FT-IR). Figure 1 As shown; X-ray diffraction (XRD) of ZIF-8, BI@ZIF-8 and BI@ZIF-8@TA was performed, and the results are shown Figure 2 As shown; Scanning electron microscopy (SEM) was performed on ZIF-8, BI@ZIF-8 and BI@ZIF-8@TA, and the results are shown Figure 3 shown.
[0029] Depend on Figure 1 and Figure 2 It can be seen that the present invention successfully prepared BI@ZIF-8 and BI@ZIF-8@TA. Figure 3It can be seen that the ZIF-8 crystal presents a regular polyhedral shape, with uniform particle size, flat and smooth, and a crystal size of about 100nm; BI@ZIF-8 is spherical, with an average particle size of 600nm; BI@ZIF-8@TA is hairy (i.e., this embodiment prepares a hairy BI@ZIF-8@TA material, whose surface has a large number of tiny dendrites (the hairy ball has a microstructure similar to the surface of a lotus leaf), which is conducive to promoting the particles to fill the resin matrix and increase the density of the coating), the surface is rough and uneven under the microscopic view (but the corresponding coating surface smoothness under the macroscopic view is excellent), and the average particle size is about 2μm. The size of ZIF-8 crystals, BI@ZIF-8 and BI@ZIF-8@TA gradually increases, and the reason is that BI and TA successively compete with 2-Melm for coordination, which gradually reduces the number of nucleation points between zinc ions and 2-Melm, resulting in the gradual increase in the size of BI@ZIF-8 and BI@ZIF-8@TA. Special note: In comparison, the surface roughness of BI@ZIF-8@TA is significantly increased (microscopic perspective). Analysis shows that the successive loading of BI and TA improves the hydrophobicity of ZIF and BI@ZIF-8, thereby significantly increasing the roughness of BI@ZIF-8@TA, which helps to increase its surface free energy and makes it easier to promote particles to fill the resin matrix and increase the density of the coating.
[0030] The particle size and micromorphology of BI@ZIF-8 and BI@ZIF-8@TA are significantly different. This result shows that TA modification has a significant effect on the particle size and micromorphology of BI@ZIF-8. The release performance of BI@ZIF-8 under different pH conditions was tested. The results are shown in Figure 4 As shown. Figure 4 It can be seen that the corrosion inhibitor BI is released rapidly within the first 3 hours of immersion. Under weak alkali and weak acid conditions, the release of the corrosion inhibitor BI reaches more than 70%. This result shows that when a corrosion reaction occurs on the surface of the metal substrate, the ZB-2 particles can quickly respond to pH and release the corrosion inhibitor BI at the corrosion reaction site, thereby slowing down the corrosion reaction of the metal substrate at the defect. In addition, the release rate of the corrosion inhibitor BI is closely related to the pH value. Compared with the condition of pH=7, the release rate of the corrosion inhibitor BI is faster under the conditions of pH=5 and pH=10 within the first 3 hours of immersion, reaching 70.4% and 72.4%, respectively. Under the condition of pH=7, the release of the corrosion inhibitor BI is relatively slow, which can avoid its large-scale leakage during the coating curing process, reduce the possibility of coating problems, and increase the reliability of its experimental data.
[0031] S2. BI@ZIF-8 and BI@ZIF-8@TA were added as fillers into epoxy resin (EP) coating; A 10 cm × 10 cm × 0.5 cm carbon steel sheet is used as a substrate for coating the self-repairing anti-corrosion coating (hereinafter referred to as carbon steel substrate).
[0032] S2.1 Adding BI@ZIF-8 as filler into EP coating Add 0.5 g of BI@ZIF-8 prepared in step S1 to 10 g of epoxy curing agent, stir for 50 min, and then perform ultrasonic treatment until uniform to obtain a mixed solution; Add 10g of epoxy resin to the mixed solution, stir evenly, and perform ultrasonic degassing treatment. Referring to GB / T20777-2006 "Inspection and Preparation of Paint and Varnish Samples", apply the coating on the surface of the pretreated carbon steel sample and cure it in an oven at 50°C for 48h. A self-healing anti-corrosion coating containing BI@ZIF-8 can be prepared on the carbon steel substrate. The obtained sample is recorded as coating sample 1.
[0033] S2.2 Adding BI@ZIF-8@TA as filler into EP coating Except that BI@ZIF-8 in step S2.1 was replaced by BI@ZIF-8@TA, a self-healing anti-corrosion coating containing BI@ZIF-8 was prepared in the same manner as S2.1 to obtain coating sample 2.
[0034] Testing the protective properties of self-healing anti-corrosion coatings: Coating sample 1, coating sample 2 and EP coating were immersed in 3.5wt.% NaCl solution respectively, and the electrochemical impedance spectroscopy (EIS) of each coating sample at different immersion periods (1d, 84d, 174d) was tested using CS310 electrochemical testing system (Wuhan Koster Instrument Co., Ltd.). The results are shown in Figure 5 , Figure 6 and Figure 7 shown.
[0035] Depend on Figure 5 It can be seen that after immersion for 1 day, the coating impedances of coating sample 1 (BI@ZIF-8), coating sample 2 (BI@ZIF-8@TA) and EP coating are very close. Figure 6 It can be seen that after 84 days of immersion, the coating impedance of coating sample 1 (BI@ZIF-8) and coating sample 2 (BI@ZIF-8@TA) is significantly greater than that of the EP coating sample, indicating that the former has better protective performance. The coating impedance value of coating sample 2 (BI@ZIF-8@TA) is significantly greater than that of coating sample 1 (BI@ZIF-8). This result shows that TA modification has a positive effect on the protective performance of the coating. Figure 7It can be seen that after immersion for 173 days, the coating impedance of coating sample 2 (BI@ZIF-8@TA) is significantly greater than that of coating sample 1 (BI@ZIF-8) and EP coating sample. This result shows that the coating prepared by the method of the present invention has excellent protective performance.
[0036] In summary, the corrosion inhibitor BI can quickly respond to the acid-base corrosion environment, with a release amount of more than 70% within 3 hours. The 3.5% NaCl immersion cycle experiment shows that the coating made of modified BI@ZIF-8@TA has excellent anti-corrosion effect.
[0037] The present invention can efficiently prepare BI@ZIF-8@TA with uniform particle size, smooth surface and regular shape under normal temperature atmospheric mixed solution environment and 70°C drying conditions. The BI@ZIF-8@TA can realize assembly and curing of the substrate and the coating under 50°C atmospheric environment. The preparation process is simple and efficient, the temperature required for crystallization and curing is low, the loaded corrosion inhibitor is green and pollution-free, the anti-corrosion effect is excellent and has a self-repairing effect.
Claims
1. A method for preparing a tannic acid modified loaded corrosion inhibitor ZIF anticorrosive filler, characterized in that: The following steps are involved: S1. Preparation of a zeolite-type imidazole acid framework loaded with benzimidazole; S2. The zeolite-type imidazole acid skeleton loaded with benzimidazole is modified with tannic acid to obtain the tannic acid-modified loaded corrosion inhibitor ZIF anti-corrosion filler.
2. The preparation method according to claim 1, characterized in that In step S1, a zeolite-type imidazole acid framework loaded with benzimidazole is prepared, comprising: adding a zinc salt-alcohol solution and a dimethylimidazole ligand-alcohol solution to a benzimidazole-alcohol solution in sequence, stirring, standing, centrifuging, washing the precipitate obtained by centrifugation, and drying to obtain the zeolite-type imidazole acid framework loaded with benzimidazole.
3. The preparation method according to claim 2, characterized in that: The mass ratio of the zinc salt to the benzimidazole is 1-1.5:0.08-0.
15.
4. The preparation method according to claim 2, characterized in that: The mass ratio of the dimethylimidazole ligand to the benzimidazole is 2-3:0.08-0.
15.
5. The preparation method according to claim 2, characterized in that: The drying temperature is 55-65° C., and the drying time is 12-36 hours.
6. The preparation method according to claim 1, characterized in that: In step S2, tannic acid is used to modify the zeolite-type imidazole acid framework loaded with benzimidazole, comprising: S2.1 dissolving the benzimidazole-loaded zeolite-type imidazole acid framework in water to obtain a suspension; S2.2 Add a tannic acid solution with a pH of 7.5-8.5 to the suspension, stir, let stand, centrifuge, wash the precipitate obtained by centrifugation, and dry to obtain the tannic acid-modified loaded corrosion inhibitor ZIF anticorrosive filler.
7. The preparation method according to claim 6, characterized in that: In step S2.2, the mass ratio of the tannic acid to the benzimidazole-loaded zeolite-type imidazole acid framework is 35-45:0.8-1.
5.
8. The preparation method according to claim 6, characterized in that: In step S2.2, the drying temperature is 65-75° C., and the drying time is 12-36 hours.
9. A tannic acid modified loaded corrosion inhibitor ZIF anticorrosive filler prepared according to the method described in any one of claims 1 to 8.
10. An anti-corrosion system, characterized in that: The invention comprises a coating substrate and a tannic acid modified loaded corrosion inhibitor ZIF anticorrosive filler prepared according to the method described in any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation method of corrosion inhibitor loaded BTA (at) ZIF-8 / BN-OH composite powder
CN115353763A
Anticorrosive filler containing two-dimensional nanosheet-point structure rust conversion, preparation method and application
CN117645811A